2002
DOI: 10.1007/s002080010018
|View full text |Cite
|
Sign up to set email alerts
|

A Rigorous ODE Solver and Smale’s 14th Problem

Abstract: Abstract. We present an algorithm for computing rigorous solutions to a large class of ordinary differential equations. The main algorithm is based on a partitioning process and the use of interval arithmetic with directed rounding. As an application, we prove that the Lorenz equations support a strange attractor, as conjectured by Edward Lorenz in 1963. This conjecture was recently listed by Steven Smale as one of several challenging problems for the twenty-first century. We also prove that the attractor is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
295
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(307 citation statements)
references
References 21 publications
4
295
0
8
Order By: Relevance
“…(11) can be analyzed with the Poincare section and the first return map. 38 Parameter c has been used to classify certain behavior of the Lorenz Eq. (11).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…(11) can be analyzed with the Poincare section and the first return map. 38 Parameter c has been used to classify certain behavior of the Lorenz Eq. (11).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Moreover, this attractor is sensitive to initial conditions and can not be destroyed by small perturbations of the original flow, that is to say it is robust. Finally, Tucker [38,39] proved the existence and robustness of the Lorenz attractor and, as a consequence of the method of his proof, showed that these models do describe the behaviour of (3.1). For more information on the history of the subject and the construction of the geometric models, we refer the reader to Araujo, Pacifico and Viana [4,40] and references therein.…”
Section: Applicationsmentioning
confidence: 98%
“…17-digit precision) to prove that the Lorenz equations support a "strange" attractor. Berkeley mathematician Steven Smale had previously included this as one of the most challenging problems for the 21st century [32].…”
Section: Computer-assisted Solution Of Smale's 14th Problemmentioning
confidence: 99%